2000
DOI: 10.1046/j.1365-277x.2000.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuing low uptake of periconceptional folate warrants increased food fortification

Abstract: Correspondence 4 Wexham Lodge,Objective To assess whether the Health Education Authority's recent promotion of periconceptional folic acid has been successful in increasing uptake sufficient to prevent neural tube defects.Design A retrospective questionnaire, completed by 162 patients in the early pregnancy clinic in Doncaster Royal Infirmary, an averagesized UK district general hospital. The study ran in February and March 1999.Methods and main outcome measures Data were collected on: supplementation and diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
1
4
0
Order By: Relevance
“…Only 16% of participants claimed to have no knowledge of folic acid. These results are analogous to a previous UK study (Sillender, 2000) where only 19% of participants had no knowledge of folic acid. It is clear that, although knowledge of the requirement for folic acid periconception is high, its use is consistently low and shows no sign of improving.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Only 16% of participants claimed to have no knowledge of folic acid. These results are analogous to a previous UK study (Sillender, 2000) where only 19% of participants had no knowledge of folic acid. It is clear that, although knowledge of the requirement for folic acid periconception is high, its use is consistently low and shows no sign of improving.…”
Section: Discussionsupporting
confidence: 88%
“…Subsequent to the introduction of the recommendations in 1992, the proportion of women using folic acid pre-pregnancy has improved from 1.8% in 1993 to 31% in 1996 (Wild et al, 1997). More recent studies have shown that preconception use of folic acid remains low (24-31%) and, although postconception use is higher (63-83%), it is thought that many women do not begin until after neural tube closure (Mathews et al, 1998;Sillender, 2000;Brooke & Doyle, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cano-Serral et al (2006) (94) ; Coll et al (2004) (95) ; Garcia (97) ; Glasgow Perinatal Effectiveness Committee (1998) (98) ; Haslam et al (2003) (99) ; Howell et al (2001) (100) ; ICM Research (2004) (101) ; Johnson (2000) (102) ; Langley-Evans & Langley-Evans (2002) (103) ; Mathews et al (1998) (104) ; Neill et al (1999) (105) ; *Relton et al (2005) (106) ; Rogers & Emmett (1998) (107) ; Sen et al (2001) (108) ; Sillender (2000) (109) ; Sillender & Pring (2000) (110) ; Wald (personal communication, 2005) USA Ahluwalia & Daniel (2001) (111) ; Alozie Arole et al (2003) (112) ; Carmichael et al (2006) (113) ; CDC (1999) (114) ; CDC (2001) (115) ; CDC (2004) (116) ; CDC (2005) (117) ; de Jong-van den Berg et al (2005) (119) ; Goldberg et al…”
Section: Spainmentioning
confidence: 99%
“…The main comparable findings are summarised in Table 4 by country. The source papers were those listed in Table 1: Australia (71)(72)(73) ; Canada (74)(75)(76)(77)(78)(79)(80) ; Croatia (81) ; Denmark (82) ; Ireland (83)(84)(85) ; The Netherlands (67,86,87) ; New Zealand (88,89) ; Norway (90)(91)(92) ; Poland (93) ; Spain (94)(95)(96) ; the UK (NJ Wald, personal communication, 2005) (97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110) ; and the USA (111)(112)(113)(114)(115)(116)…”
Section: Spainmentioning
confidence: 99%
“…This percentage is small in comparison to other studies. For example in a Canadian study, 95% of the participants reported having heard of folate (French at al., 2003) and in a UK study 81% of women were aware of the benefits of folic acid (Sillender, 2000). In a US study conducted with Hispanic women in Texas, 78% of mothers knew about folic acid (Canfield et al, 2006).…”
Section: Discussionmentioning
confidence: 97%